Strategic Litigation as a Framework for the Protection of Indigenous Rights. An Analysis of Some of the Achievements, Difficulties and Challenges Involved - Asier Martínez de Bringas (Age of Human Rights Journal, 2020)
This study is structured into two clearly defined sections. Firstly, strategic litigation will be used as a framework to account for the developments and improvements made to indigenous rights as a result of the remarkable international effort to protect indigenous peoples. Some focal points in the production of strategic litigation discourse on indigenous rights and its guarantees will be considered. These will include the discourse produced by the United Nations and its related institutions in recent years specifically to solve the dramatic situation of indigenous peoples; and the discourse by the Inter-American Court of Human Rights (under the regional aegis of the OAS). Secondly, these developments will be contrasted with a crude diagnosis of reality by identifying the main difficulties and the real limits for the consolidation and implementation of indigenous rights. This will be followed by an outline of the challenges to be faced by indigenous peoples in the coming years, which will compel them to try new ways of political, normative, and strategic thinking.